The hydrologic landscape of the Ajó coastal plain, Argentina: An assessment of human-induced changes. (June 2017) - Carol, E.; Braga, F.; Donnici, S.; Kruse, E.; Tosi, L.
Highlights: Human-induced processes change the hydrological landscape in Ajó coastal plain. Remote sensing applied to the identification of ancient river structures. Historical maps highlighted the changes occurred over the last 120 yr. The synergy of the human-made interventions condition the hydrological wetland landscape. Abstract: Coastal wetlands rank among the most endangered ecosystems since they are affected by the sea level rise and by anthropogenic activities. The continued loss and degradation of these valuable environments requires greater understanding of groundwater–surface water exchange, as the ecological function of coastal wetlands greatly depends on it. Hydrological research carried out in the lower part of the Samborombón Bay coastland (Río de la Plata estuary, Argentina) by remote sensing revealed the presence of a meandering channel system, which does not appear in modern maps. Analysis of SPOT satellite images and interpretation of historical maps and in situ surveys confirmed that this structure is part of an ancient river system – the palaeo-Rincón de Ajó River – at present almost completely silted up. In addition, multispectral satellite data provided information to develop a conceptual hydrological model, as well as evidence that a significant hydrologic landscape shift occurred due to human-made interventions. The palaeo-Rincón de Ajó River disappeared because water flow in its upper course was intercepted by human-made canals. In its lower course, embankments built for the construction of roads and flood prevention of the wetlands from the Río de la Plata estuary excluded the surface flow from the estuary to the mainland and vice versa. The silting up in the lower course and in the vicinity of the mouth cancelled the original structure of the ancient river.